AN INVESTIGATION INTO TEACHERS’ DIFFICULTIES IN TEACHING SPEAKING AT PHAN CHAU TRINH HIGH SCHOOL, DA NANG - Trần Phạm Hoài Nguyên (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study was carried out to investigate the difficulties in teaching speaking of teachers at Phan Chau Trinh High school, Da Nang. The study examined the reality of speaking and learning speaking at Phan Chau Trinh High school, the research finds out the difficulties which English teachers at Phan Chau Trinh high school are facing with, the causes of the problems as well as explored effective suggestions to help enhance the effectiveness of speaking periods. The study employed qualitative research method, using questionnaires and observation as the technique of data collection. The findings of the research showed that students at Phan Chau Trinh performed differently during speaking classes, which was a challenge for teachers to conduct effective speaking periods. Teachers suffered from a variety of problems such as students’ attitude to speaking class, time limitation, lesson plan, way to motivate students. The causes of those problems came from students, external factors and the teachers themselves. To help enhance the effectiveness of speaking periods, teachers has recommended some suggestions namely motivating students, using pair work and group work and so on